Association between Dietary Macronutrient Intake and High-Sensitivity C-Reactive Protein Levels among Obese Women in Kuantan, Malaysia - Shahadan, Siti Zuhaidah; Daud, Azlina; Ibrahim, Muhammad; Md. Isa, Muhammad Lokman; Draman, Samsul (Makara Journal of Science, 2020)
Elevated high-sensitivity C-reactive protein (hs-CRP) levels may be associated with an increased risk of cardiovascular disease (CVD). In general, an individual’s dietary intake may influence the hs-CRP level. However, evidence on the influence of dietary macronutrient intake on hs-CRP levels among obese Malaysian women remains fragmented. Therefore, this study aims to investigate the association between the hs-CRP level and dietary macronutrient intake of obese adults living in Kuantan. The assessment of 24-hour dietary recall and venous hs-CRP levels were investigated in 67 women with a body mass index of 27.5 to 39.9 kg/m². The findings revealed that obese women living in Kuantan had elevated hs-CRP levels (median = 7.95 mg/L, IQR = 7.90) and a significant negative correlation between the hs-CRP level and total dietary fiber intake (r = 0.205, p =.014). In conclusion, this study suggests that certain macronutrients, particularly dietary fiber, seem to be associated with elevated hs-CRP in obese women. Hence, this information could help assess and manage low-grade chronic inflammation and underlying obesity-related conditions.